2023
DOI: 10.1002/acn3.51890
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and mathematical modeling of longitudinal CSF differentiates fast versus slow ALS progression

Lucas Vu,
Krystine Garcia‐Mansfield,
Antonio Pompeiano
et al.

Abstract: ObjectiveAmyotrophic lateral sclerosis (ALS) is a heterogeneous disease with a complex etiology that lacks biomarkers predicting disease progression. The objective of this study was to use longitudinal cerebrospinal fluid (CSF) samples to identify biomarkers that distinguish fast progression (FP) from slow progression (SP) and assess their temporal response.MethodsWe utilized mass spectrometry (MS)‐based proteomics to identify candidate biomarkers using longitudinal CSF from a discovery cohort of SP and FP ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We performed Mann-Whitney statistical testing with adjusted p-value cutoffs (at the false positive rate α = 0.05 level of significance) within each tissue using the Benjamini-Hochberg procedure, and found that SOD1 trimers selectively and significantly bound one protein in the brain (septin-7; p = 0.00045), five proteins in the spinal cord (cytochrome c oxidase; p = 0.0012, creatine kinase; p = 0.00012, brain acid soluble protein 1; p = 0.0019, microtubule-associated protein 1; p = 0.018, and hemoglobin sub unit alpha; p = 0.018) and one protein in skeletal muscle (fructose-bisphosphate aldolase A; p-adjusted <0.0001) (Table 1). Notably, septin-7 3234 , brain acid soluble protein 1 35,36 , and fructose-bisphosphate aldolase A 37,38 are tissue-specific protein hits and have been previously linked to neurodegenerative processes. Overall, SOD1 trimers feature tissue-selective interactomes compared to that of native SOD1 dimers.…”
Section: Resultsmentioning
confidence: 99%
“…We performed Mann-Whitney statistical testing with adjusted p-value cutoffs (at the false positive rate α = 0.05 level of significance) within each tissue using the Benjamini-Hochberg procedure, and found that SOD1 trimers selectively and significantly bound one protein in the brain (septin-7; p = 0.00045), five proteins in the spinal cord (cytochrome c oxidase; p = 0.0012, creatine kinase; p = 0.00012, brain acid soluble protein 1; p = 0.0019, microtubule-associated protein 1; p = 0.018, and hemoglobin sub unit alpha; p = 0.018) and one protein in skeletal muscle (fructose-bisphosphate aldolase A; p-adjusted <0.0001) (Table 1). Notably, septin-7 3234 , brain acid soluble protein 1 35,36 , and fructose-bisphosphate aldolase A 37,38 are tissue-specific protein hits and have been previously linked to neurodegenerative processes. Overall, SOD1 trimers feature tissue-selective interactomes compared to that of native SOD1 dimers.…”
Section: Resultsmentioning
confidence: 99%
“…Constructing a state-space to model biological transitions can capture changes produced by genetic, epigenetic, or microenvironmental perturbations on the transcriptome, which simultaneously deregulate multiple biological processes in order to generate a phenotype such as the leukemic transformation observed here [ 26 29 ]. We have previously shown that micro-RNA and protein abundance (proteomic) data can also be used to create a state-space and characterize state-transitions [ 10 , 30 ]. Using a transgenic CP CML mouse model that recapitulated the human disease, we report here the application of state-transition theory to interpret the temporal transcriptomic changes involved both in CML development and in treatment (where CML is “reversed”) to accurately predict outcome and treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…In another study from Vu et al, the authors identified a list of proteins differentially expressed between fast and slow progressors. Interestingly, proteins associated with fast progressors were part of the immune response pathway, while pathways related to synaptogenesis and glycolysis/gluconeogenesis were downregulated [ 44 ]. These two studies again highlight the importance of monitoring the immune response pathway for ALS clustering.…”
Section: Molecular Heterogeneitymentioning
confidence: 99%
“…These two studies again highlight the importance of monitoring the immune response pathway for ALS clustering. Interestingly, while transcriptomic clustering did not succeed in explaining patient clinical profile, proteomic clustering demonstrated some correlation with some clinical features (concomitant cognitive impairment, progression rate) [ 43 , 44 ]. Thus, studying the proteomic profile of ALS patients might give access to more pertinent information.…”
Section: Molecular Heterogeneitymentioning
confidence: 99%